ANALISIS KUALITAS PELAYANAN PADA ANJUNGAN DKI JAKARTA TAMAN MINI INDONESIA INDAH - Ryan Sebastian; I Made Kusuma Negara; I Putu Sudana (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2013)
The title of this final report is “ Analysis Of service Quality In jakarta pavilion Taman Mini Indonesia Indah”. The background of this research is the decrease of service provide to tourist . Tourist destination should be able to give good service to the tourist. by giving good service, will creating satisfaction for tourist enjoying attraction and culture in the Jakarta pavilion Taman Mini Indonesia Indah The target of this research is to know about perception of tourist to the service quality of staff or guide in the pavilion Jakarta . Kinds of that are used are qualitative and quantitative, data source are primary data and secondary data, data collection by observation, deep interview, questionnaire and literary study. Technic of data analysis that is used descriptive qualitative and likert scale analysis. The result of the study is perception of tourist to the service quality of staff and guide in the Jakarta pavilion is netral which means is not good or not bad with average of all is 3,45 from 50 respondents. The suggestion that can be given to the management of pavilion Jakarta the effort to the quality of service to improve the staff and guides quality in Jakarta pavilion.